Design and Implementation of an Extranet Web Application for Collaborative Education at the Faculty of Sciences and Techniques – Comoros (American Journal of Interdisciplinary Research and Innovation, 2024)
This paper presents an interactive e-learning web platform for the Faculty of Sciences and Techniques, University of Comoros. This Extranet application replaces the manual Excel processing during session examination by proposing a fully automated programming application. The proposed platform helps to minimize errors that occur when using Excel manipulation, students’ interaction with the department, and waiting time before a response. The application leads also to a centralization of the results after deliberation and students can consult their detailed results over the different islands without having to come back to the campus. For the security of the developed platform, we used the well-known efficient agile method that allows us to facilitate task management during the process. The full platform was designed using the UML, and the implementation was done under object-oriented programming. The system was built using PHP, HTML, CSS, Symfony, JavaScript, and MySQL. For the Extranet considerations, all users are given a non-modifiable username and a unique password to access the application. During the testing period, the administration service was able to accept student requests such as reports and attestation, and scores claiming and students were automatically notified of the evolution of their requests.